Risk factors for therapy failure after surgery for perianal abscess in children - Doerner, Johannes; Seiberth, Rose; Jafarov, Sakhavat; Zirngibl, Hubert; Boenicke, Lars (Frontiers in Surgery, 2022)
Purpose The role of surgery in managing perianal abscesses in the pediatric population is debatable, and data on recurrence risk is rare. This study aimed to evaluate the efficiency of surgery for a perianal abscess in children and identify parameters that predict recurrence. Methods We performed a retrospective review of all children younger than age 14 requiring surgery for a perianal abscess from 2000 to 2018. Results Out of 103 enrolled patients, 27 (26%) had recurrent perianal disease. Recurrences appeared after a median of 5 months (range: 1–18 months), in 12 cases as perianal abscess and 15 cases as fistula in ano. Anal fistula probing was performed in 33% of all patients, of which 16 (15%) underwent fistulotomy. In univariate analysis, older age (p = 0.034), fistula probing (p = 0.006) and fistulotomy (p = 0.009) was associated with treatment success. History of perianal abscess, multilocal occurrence, and the presence of enteric flora in wound swabs was associated with treatment failure (p = 0.002, OR = 0.032). In multivariate analysis, anal fistula probing was independently associated with treatment success (p = 0.019, OR = 22.08), while the history of perianal abscess was associated with treatment failure (p = 0.002, OR = 0.032). Conclusion Our study identified probing for fistula as a predictor of therapy success, while the history of perianal abscess was identified as a predictor of treatment failure. Therefore, in all children with perianal abscess, fistula probing and if present, fistulotomy should be performed.